Oral verrucous carcinoma: a 24-year epidemiological study and case report - Silva, Iago Demétrio da; Tolentino, Elen de Souza; Camarini, Camila; Berlin, Eloise Girondi; Veltrini, Vanessa Cristina; Silva, Mariliani Chicarelli da; Lobo, Fernanda (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Introduction: Verrucous carcinoma is a non-metastatic variant of squamous cell carcinoma. It was first reported by Ackerman in 1948. It is a verrucous exophytic tumor and, although it is a rare lesion, it mainly affects the oral cavity, with slow growth and can be locally invasive. Objective: To report a case and present an observational and retrospective analysis of medical records containing biopsy data from patients diagnosed with oral verrucous carcinoma (OVC) in an oral diagnostic referral service for a period of 24 years. Material and methods: The following data were collected: age, sex, ethnicity, anatomical location and management. Result: Eight cases of OVC were found, all in Caucasian patients (n = 8, 100%), aged between 57 and 102 years. 62% of the injuries affected women. The most affected region was the jugal mucosa (n = 4, 50%). In addition, Smoking patients were not found. In all cases, incisional biopsy was performed and referral to the head and neck surgeon. Conclusion: Caucasian women in the sixth and seventh decades of life were the most affected by OVC. The absence of smoking patients corroborates the literature, which reports that cigarettes appear to be unrelated to this injury. The dentist's role is to recognize the disease early, diagnose it and refer it for medical treatment.